CO-PRODUCTION OF INNOVATIVE PUBLIC SERVICES – A THEORETICAL BACKGROUND - Kobylińska, Urszula (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Co-production is currently one of the pillars of the public sector reform around the world. The potential of this concept is increasingly recognized in the design and improvement of public services in cities. Co-production is a partnership among citizens, public institutions and enterprises, which enables all the parties to be more involved in the management of the city and contributes to greater control over public resources (Horne, Shirley, 2009). In the subject literature, it is pointed out that these reforms are directed to the implementation of effective public services, are a response to the deficit of active citizenship and active communities and enterprises that are insufficiently involved in the processes of designing and co-creating innovative public services in cities. The basic - and basically still valid today - conceptualization of co-production was carried out in several works published in the first half of the 1980s. The aim of this paper is to analyse the state of research on the issue of co-production in public services and to identify the main research areas related to this subject. The paper was based on a systematic review of literature, which included, among others, the emergence of basic literature and selection of publications, bibliometric analysis and content analysis. The results of the conducted research show that the issue of co-production in public services is a new subject, still not well recognized in the literature and which may constitute a current and interesting area of research.